A Practical and Time-Efficient High-Intensity Interval Training Program Modifies Cardio-Metabolic Risk Factors in Adults with Risk Factors for Type II Diabetes - Phillips, Bethan E.; Kelly, Benjamin M.; Lilja, Mats; Ponce-González, Jesús Gustavo; Brogan, Robert J.; Morris, David L.; Gustafsson, Thomas; Kraus, William E.; Atherton, Philip J.; Vollaard, Niels B. J.; Rooyackers, Olav; Timmons, James A. (Frontiers in Endocrinology, 2017)
Introduction Regular physical activity (PA) can reduce the risk of developing type 2 diabetes, but adherence to time-orientated (150 min week−1 or more) PA guidelines is very poor. A practical and time-efficient PA regime that was equally efficacious at controlling risk factors for cardio-metabolic disease is one solution to this problem. Herein, we evaluate a new time-efficient and genuinely practical high-intensity interval training (HIT) protocol in men and women with pre-existing risk factors for type 2 diabetes. Materials and methods One hundred eighty-nine sedentary women (n = 101) and men (n = 88) with impaired glucose tolerance and/or a body mass index >27 kg m−2 [mean (range) age: 36 (18–53) years] participated in this multi-center study. Each completed a fully supervised 6-week HIT protocol at work-loads equivalent to 100 or 125% V˙O2 max. Change in V˙O2 max was used to monitor protocol efficacy, while Actiheart™ monitors were used to determine PA during four, weeklong, periods. Mean arterial (blood) pressure (MAP) and fasting insulin resistance [homeostatic model assessment (HOMA)-IR] represent key health biomarker outcomes. Results The higher intensity bouts ( 125% V˙O2 max) used during a 5-by-1 min HIT protocol resulted in a robust increase in V˙O2 max (136 participants, +10.0%, p < 0.001; large size effect). 5-by-1 HIT reduced MAP ( 3%; p < 0.001) and HOMA-IR ( 16%; p < 0.01). Physiological responses were similar in men and women while a sizeable proportion of the training-induced changes in V˙O2 max, MAP, and HOMA-IR was retained 3 weeks after cessation of training. The supervised HIT sessions accounted for the entire quantifiable increase in PA, and this equated to 400 metabolic equivalent (MET) min week−1. Meta-analysis indicated that 5-by-1 HIT matched the efficacy and variability of a time-consuming 30-week PA program on V˙O2 max, MAP, and HOMA-IR. Conclusion With a total time-commitment of <15 min per session and reliance on a practical ergometer protocol, 5-by-1 HIT offers a new solution to modulate cardio-metabolic risk factors in adults with pre-existing risk factors for type 2 diabetes while approximately meeting the MET min week−1 PA guidelines. Long-term randomized controlled studies will be required to quantify the ability for 5-by-1 HIT to reduce the incidence of type 2 diabetes, while strategies are required to harmonize the adaptations to exercise across individuals.